2022
DOI: 10.1016/j.jhep.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD vs. MAFLD – It is not the name but the disease that decides the outcome in fatty liver

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…NAFLD is diagnosed by exclusion; it is defined as hepatic steatosis not secondary to specific causes such as viral infection, alcohol consumption, or drug‐related liver damage, and its prevalence is increasing 2 . In contrast to NAFLD, metabolic‐associated fatty liver disease (MAFLD) is defined more inclusively by focusing on the prognosis in relation to fatty liver disease (e.g., including those who regularly consume alcohol or have viral hepatitis) 3 . The diagnostic value of MAFLD is reportedly superior to that of NAFLD; individuals with MAFLD are found to be at high risk not only for hepatic lesions such as hepatic fibrosis but also for extra‐hepatic disease development such as cardiovascular disease, malignancy, and ultimately mortality 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAFLD is diagnosed by exclusion; it is defined as hepatic steatosis not secondary to specific causes such as viral infection, alcohol consumption, or drug‐related liver damage, and its prevalence is increasing 2 . In contrast to NAFLD, metabolic‐associated fatty liver disease (MAFLD) is defined more inclusively by focusing on the prognosis in relation to fatty liver disease (e.g., including those who regularly consume alcohol or have viral hepatitis) 3 . The diagnostic value of MAFLD is reportedly superior to that of NAFLD; individuals with MAFLD are found to be at high risk not only for hepatic lesions such as hepatic fibrosis but also for extra‐hepatic disease development such as cardiovascular disease, malignancy, and ultimately mortality 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to NAFLD, metabolic‐associated fatty liver disease (MAFLD) is defined more inclusively by focusing on the prognosis in relation to fatty liver disease (e.g., including those who regularly consume alcohol or have viral hepatitis) 3 . The diagnostic value of MAFLD is reportedly superior to that of NAFLD; individuals with MAFLD are found to be at high risk not only for hepatic lesions such as hepatic fibrosis but also for extra‐hepatic disease development such as cardiovascular disease, malignancy, and ultimately mortality 3,4 . In particular, among the Japanese population, comorbid MAFLD has recently been reported to be associated with atherosclerotic cardiovascular risk, colorectal adenoma, and reflux esophagitis 5–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cross-sectional studies, there were a few studies that showed little to no difference in the prevalence of increased fibrosis risk in all MAFLD+ NAFLD+ (overlapping diagnosis) patients. Particularly, the lack of diagnostic data recorded for the 3 categories of MAFLD resulting in the exclusion of many MAFLD+ patients has been highlighted [ 53 ]. This is an important gap that future MAFLD clinical studies need to fill to obtain a clearer picture of the MAFLD-NAFLD landscape.…”
Section: Clinical Landscape With New Mafld Criteriamentioning
confidence: 99%
“…The diagnostic criteria of MAFLD include hepatic steatosis in addition to obesity, T2DM, or metabolic dysfunction [7]. However, there is a debate that the criteria of MAFLD are poorly applicable in real clinical practice as some non-obese, non-diabetic patients with hepatic steatosis could not be diagnosed due to the lack of laboratory tests for metabolic dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%